1 - All Knowledge Is first of all Local Knowledge: An Introduction: DOI: 10.4314/ad.v30i3.22226 - Njoku, Chukwudi Anthony; Devisch René (Africa Development, 2005)
Against a monolithic view of knowledge production and the tendency to universalize science, this article calls attention to the unique genius and distinctive creativity and originality which underlines production of knowledge in any given cultural context. It takes seriously, the fact that, at its roots, knowledge production is context bound. Hence the authors emphasize the fact that all knowledge is first of all local knowledge. From this fundamental understanding of the true wellsprings of the production of knowledge, it argues against a mythic veil, which reformist modernity, especially, tended to place on the process of producing and transmitting knowledge. This deceptive myth about knowledge production, it opines, has had the negative impact of stereotyping, blackmailing, inferiorizing and derailing the production and sharing of knowledge and its artefacts in cultures other than the West. The colonial encounter, with its assumptions and presumptions, helped to rub in this vision of reformist modernity and to muffle the voices of colonised cultures. Hence such labels as 'indigenous' knowledge. In recognition, therefore, of the creative and genuine originality latent in every culture, this article seeks to empower cultures to realise, work on and appropriate the riches embedded in their own local knowledge tracts and trajectories. This appropriation by cultures, of their own rich genius, is, for the authors, the gateway to re-acquiring cultural dignity and self-confidence and indeed an opportunity for each cultural node to positively contribute to the commonwealth of world knowledge. Such variegated approach to mining the wisdom and ecological advantages of various cultural groups will enhance the sharing of knowledge in a spirit of both vertical and horizontal border-linking exchanges of riches found in different cultural contexts and knowledge fields. The ancient wisdom of the Igbo of south eastern Nigeria is used in the article as an illustration of this latent, culture specific genius. The article also highlights the mission of Whelan Research Academy for Religion, Culture and Society, Owerri, Nigeria, in creating awareness, space and forum for paying closer attention to indigenous knowledge tracts endangered in this derailment of a wider spectrum of cultural nodes of knowledge.